Goal Orientation and Learning Readiness: Evidence Among Freshmen in Selected Kenyan Universities - Mose, Evelyne Kwamboka; Aloka, Peter JO; Mwebi, Benard (Alberta Journal of Educational Research, 2022)
This study, which adopted an ex post facto research design, investigated the relationship between goal orientation and learning readiness among first year students in three public universities in Kenya. A sample size of 372 first years from the three universities were obtained using both stratified and simple random sampling techniques. The Goal Questionnaire for Students (GQS) and the Learning Readiness Questionnaire (LRQ) were used to collect data. The findings reported Eta squared (.547) which implied that a fairly large proportion (54.7%) of variance in he learning readiness index among the first year students is explained by goal orientation of the students. Results from the study determined that universities should emphasize techniques of performance approach in their guidance programs. Key words: Goal Orientation, Learning Readiness, first year, students, universities, Kenya Cette étude, qui a adopté une conception de recherche ex post facto, a examiné la relation entre l'orientation vers un objectif et la préparation à l'apprentissage chez les étudiants de première année dans trois universités publiques du Kenya. Un échantillon de 372 étudiants de première année des trois universités a été obtenu en utilisant des techniques d'échantillonnage aléatoire simple et stratifié. Le Goal Questionnaire for Students (GQS) et le Learning Readiness Questionnaire (LRQ) ont été utilisés pour collecter les données. Les résultats font état d'un coefficient Eta carré (.547) qui implique qu'une proportion assez importante (54,7%) de la variance de l'indice de préparation à l'apprentissage chez les étudiants de première année s’explique par l'orientation des objectifs des étudiants. Les résultats de l'étude ont déterminé que les universités devraient mettre l'accent sur les techniques d'approche de la performance dans leurs programmes d'orientation. Mots clés: orientation vers un but, préparation à l'apprentissage, première année, étudiants, universités, Kenya